Thermally Induced Ion Magnetic Moment in H4O Superionic State - Xiao Liang; Junhao Peng; Fugen Wu; Renhai Wang; Yujue Yang; Xingyun Li; Huafeng Dong (Crystals)
The hydrogen ions in superionic ice can move freely, playing the role of electrons in metals. Its electromagnetic behavior is the key to explaining the anomalous magnetic fields of Uranus and Neptune. Based on an ab initio evolutionary algorithm, we searched for the stable H4O crystal structure under pressures of 500–5000 GPa and discovered a new layered-chain Pmn21-H4O structure with H3 ion clusters. Interestingly, H3 ion clusters rotate above 900 K (with an instantaneous speed of 3000 m/s at 900 K), generating an instantaneous magnetic moment (~10−26 A·m2 ≈ 0.001 <semantics>μB</semantics>). Moreover, H ions diffuse in a direction perpendicular to the H-O atomic layer at 960–1000 K. This is because the hydrogen–oxygen covalent bonds within the hydrogen–oxygen plane hinder the diffusion behavior of H3 ion clusters within the plane, resulting in the diffusion of H3 ion clusters between the hydrogen–oxygen planes and the formation of a one-dimensional conductive superionic state. One-dimensional diffusion of ions may generate magnetic fields. We refer to these two types of magnetic moments as “thermally induced ion magnetic moments”. When the temperature exceeds 1000 K, H ions diffuse in three directions. When the temperature exceeds 6900 K, oxygen atoms diffuse and the system becomes fluid. These findings provide important references for people to re-recognize the physical and chemical properties of hydrogen and oxygen under high pressure, as well as the sources of abnormal magnetic fields in Uranus and Neptune.